2021
DOI: 10.1016/j.jsxm.2021.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Frequency and Patterns of Marital Sexual Activity During COVID-19: Evidence from Longitudinal Data Prior to, During and After Lockdown in Singapore

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 42 publications
0
6
0
3
Order By: Relevance
“…Poor quality of sexual life was also associated with low self-esteem and poor physical and mental health. Similarly, the study by Tan et al [40] indicated that stress, fatigue, and low marital satisfaction levels were significant predictors of low sexual activity among Singaporeans. Among Polish participants, a lower frequency of sexual intercourse was related to pandemic-induced fatigue and stress and the permanent presence of others at home [44].…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…Poor quality of sexual life was also associated with low self-esteem and poor physical and mental health. Similarly, the study by Tan et al [40] indicated that stress, fatigue, and low marital satisfaction levels were significant predictors of low sexual activity among Singaporeans. Among Polish participants, a lower frequency of sexual intercourse was related to pandemic-induced fatigue and stress and the permanent presence of others at home [44].…”
Section: Discussionmentioning
confidence: 80%
“…It is also important to note that some other studies reported positive changes in sexual behavior [38][39][40][41][42][43] and higher assessment of sexual satisfaction [42,44] during the COVID-19 pandemic. Arafat et al [38] found that 45% of the respondents from three Asian countries (Bangladesh, India and Nepal) reported that the lockdown impacted their sexual life.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The exclusion criteria were those who were younger that 18 years old and postmenopausal women. The questionnaire was developed in English, based on the literature [22,23], and then translated into Arabic by a professional translator. The questionnaire was pilot-tested randomly on 30 women.…”
Section: Study Design and Populationmentioning
confidence: 99%